The Effect of Different Approaches to Learning Strategy Instruction on Vocabulary Development by EFL learners - DARIN NSHIWI (Universitas Jambi, Indonesia, 2020)
This research falls within the area of teaching English as a foreign language (FL). It focuses on the short-term effects of memory and cognitive strategies on learning vocabulary and sheds light on the approaches adopted by EFL teachers while teaching these strategies. It investigates whether these strategies are taught implicitly, explicitly or both. To conduct this study, two main tools were applied: the first was a questionnaire to evaluate the memory and cognitive strategies used by EFL teachers and intermediate learners; the second was a vocabulary test to investigate the effect of using memory and cognitive strategies on vocabulary learning. These tools were applied to the sample that included 36 intermediate learners who were divided into experimental and control groups and 30 EFL teachers. The data obtained was dealt with descriptively and analytically. The findings show that training students to use memory and cognitive strategies explicitly enhances vocabulary learning more than implicit instruction.